2019
DOI: 10.1073/pnas.1908079116
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune antibodies correlate with immune checkpoint therapy-induced toxicities

Abstract: Immune checkpoint (IC) therapy provides substantial benefits to cancer patients but can also cause distinctive toxicities termed immune-related adverse events (irAEs). Biomarkers to predict toxicities will be necessary to improve management of patients receiving IC therapy. We relied on serological analysis of recombinant cDNA expression libraries to evaluate plasma samples from patients treated with IC therapy and identified autoantibodies, both in pretreatment and on-treatment samples prior to the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 44 publications
1
141
2
1
Order By: Relevance
“…Some researchers managed to find organ-specific autoantibodies, but this is more likely due to the development of a chronic disease. Researchers of the Salahaldin A. Tahira group determined the organ-specific antibodies in the development of hypophysitis, namely anti-GNAL and anti-ITM2B, and pneumonitis, anti-CD74 [ 117 ], while antibodies to thyroperoxidase are used for autoimmune thyroiditis diagnosis [ 118 ]. Despite the contradictory results, some authors suggest using ANA, anti-smooth muscle antibody, for the diagnosis of liver damage.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…Some researchers managed to find organ-specific autoantibodies, but this is more likely due to the development of a chronic disease. Researchers of the Salahaldin A. Tahira group determined the organ-specific antibodies in the development of hypophysitis, namely anti-GNAL and anti-ITM2B, and pneumonitis, anti-CD74 [ 117 ], while antibodies to thyroperoxidase are used for autoimmune thyroiditis diagnosis [ 118 ]. Despite the contradictory results, some authors suggest using ANA, anti-smooth muscle antibody, for the diagnosis of liver damage.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…In regard to ICI-mediated hypophysitis, one study showed serial increases in autoantibodies to the proteins GNAL and ITM2B in patients treated with ipilimumab. ZCCHC8 autoantibodies were not increased in this discovery cohort (9). Our study showed that patient 1 had a 2.4-fold increase in ITM2B and patient 2 had no ITM2B increases.…”
Section: Discussionmentioning
confidence: 42%
“…These arrays identify patterns of autoantibody response against a large number of antigens during the course of development of diseases, such as autoimmunity or malignancy (4)(5)(6). Protoarray studies have shown that certain autoantibodies may predict ICI toxicity (7,8), but only one recent study has examined autoantibody changes in hypophysitis specifically, showing increases in the autoantibodies GNAL and ITM2B in 8 patients (including melanoma, prostate cancer, and renal cell carcinoma) (9).…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies against TSH-, FSH-, or ACTH-producing cells have been detected in patients with ipilimumab-induced hypophysitis (45). A screening using cDNA expression libraries of the plasma samples identified anti-olfactory type G-protein alpha-activating activity polypeptide (GNAL) antibody and anti-integral membrane protein 2B (ITM2B) antibody in ICI-induced hypophysitis (48). Although the pathophysiological role of these antibodies is still unclarified, it has been suggested that the anti-GNAL autoantibody has the potential to act as both a predictive and an on-treatment biomarker for ICI-induced hypophysitis, whereas the anti-ITM2B autoantibody has the potential to act as an on-treatment biomarker for ICI-induced hypophysitis (48).…”
Section: Ici-induced Hypophysitismentioning
confidence: 99%